Plastic and Reconstructive Surgery in Personalized Medicine - Arkudas, Andreas; Horch, Raymund (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Plastic and reconstructive surgery has a broad spectrum of different reconstructive techniques, including split skin transplantation and local and free flaps. By means of microsurgery and perforator flaps, every reconstructive issue can be addressed by tailored techniques. Flaps can comprise different tissues and can be designed using new imaging technologies in order to increase the safety of the procedures and to retain the form and function of the reconstructed area in accordance with the donor site morbidity. This Special Issue of the Journal of Personalized Medicine focuses on the following topics:Individualized microsurgery;Flap imaging;Customized perforator flaps;Monitoring flap perfusion;Tailored tissue engineering for reconstruction;Biofabrication applications in personalized plastic and reconstructive surgery.